Motor and thermodynamic losses in linear cryocooler compressors - Reed, J; Bailey, P; Daddl, M; Davis, T (2006)
Stirling cycle and Pulse Tube cryocoolers can be described by ideal thermodynamic cycles with discrete losses, however experiments show a systematic underestimate of power consumed. Existing correlations have been unable to explain the magnitude of this additional 'compression loss', but it can account for up to 50% of the power delivered to the gas. It appears that even a modest decrease could significantly improve the efficiency of future machines. One problem inherent in studying this effect is the complex geometry of cryocoolers. Experiments have therefore been performed on an existing 'Oxford type' moving coil compressor with the simplest compression space geometry, a flat cylinder head. Measurements were made of the intrinsic motor losses (including windage), and the power delivered to the gas. The results show that for this machine the motor losses are greater than previously thought, accounting for up to 30% of the compression loss in the original cryocooler configuration. Measurements of the heat transfer losses are also presented. © 2006 American Institute of Physics.